Fundamentalisme dan Inklusivisme dalam Paradigma Perubahan Keagamaan - Maimun Fuadi (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Fundamentalism is a historical phenomenon in the discourse of religious thoughts, in where Islam is included in. The association of fundamentalism to a group tends to picture the negative impact in its development process. Radicalism, militant, terrorism, and exclusivism color and are strongly attached to Islamic fundamentalism. In fact, since its invention, Islam calls for open minded and inclusivism in practicing the religion teachings. For that, the change of paradigms particularly in relation with religious understanding – such as Islamic fundamentalism – is a process that requires bravery, vision, and specially clear and pure mind in understanding spirit of God’s teachings. These are required by Islamic fundamentalism to actualize earthly prosperity and peace.